Discovering, deciphering and dissenting Ben Sira Manuscripts after 120 years - Aitken, J. K. 1968-2023; Egger-Wenzel, Renate 1961-; Reif, Stefan C. 1944-; Walter de Gruyter GmbH & Co. KG (Boston De Gruyter, 2018)
Introduction -- I. Discovery and disputes -- Notes on Jumbo's desk -- Charles Taylor as a man of St John's -- How Ben Sira crossed my path -- II. The Hebrew manuscripts and rabbinic circles -- Some first editions of Genizh manuscripts of Ben Sira -- The "booklet" of Ben Sira -- Scribal practices in Ben Sira manuscript B -- The Persian glosses and the text of manuscript B revisited -- The synoptic problem and the reception of the Ben Sira manuscripts -- Various attempts at producing a Ben Sira polyglo -- Ben Sira-biblical sage, rabbi, and payyet̲an -- Ben Sira: a rabbinic perspective -- III. The poetry of the book -- The poetry of Ben Sira manscript C -- Ben Sira's Hebrew poetry in comparison with the psalter -- Poetic imagery in the book of Ben Sira -- The theological and philosophical concepts of Ben Sira -- IV. The language of the book -- The Hebrew of the Ben Sira manuscripts from the genizah -- Transmission and transformation of Ben Sira's poetic language -- The contribution of the language of the book of Ben Sira to biblical Hebrew philology -- Biographies of authors -- Index of references -- Index of authors -- Index of subjects.
Includes bibliographical references and indexes
Keywords: Bible -- Manuscripts; Bible; Manuscripts; RELIGION / Biblical Studies / Bible Study Guides; Electronic books; Aufsatzsammlung